Investigation of renal lesions by diffusion-weighted magnetic resonance imaging applying intravoxel incoherent motion-derived parameters: initial experience - Rheinheimer, Stephan; Pahernik, Sascha; Kauczor, Hans-Ulrich; Hallscheidt, Peter (European journal of radiology, 2012)
Purpose Usefulness of biexponentially fitted signal attenuation at different b-values for differentiating the histological characteristics of renal tumors. Materials and methods A total of 26 patients with 28 renal masses (histologically proven: 20 clear cell renal cell carcinomas [ccRCC], three transitional cell carcinomas, two oncocytomas, and one papillary RCC) and 30 volunteers with healthy kidneys were examined at 1.5Tesla using an echo-planar DWI sequence. Using the IVIM model, we calculated the perfusion fraction f and the diffusion coefficient D. Furthermore, the ADC was obtained. These tumor parameters were compared to healthy renal tissue nonparametrically, and a receiver operating characteristic (ROC) analysis was performed. Results Healthy renal parenchyma showed higher ADC and D values (p<0.001) than ccRCC (ADC 1.95±0.10 [SD]μm2/ms, f 18.32±2.52%, and D 1.88±0.11μm2/ms versus ADC 1.45±0.38μm2/ms, f 18.59±6.16%, and D 1.34±0.38μm2/ms). When detecting malignancies the area under the curve for D was higher than for ADC. The f values for ccRCC were higher (p<0.001) than for non-ccRCC (ADC 1.52±0.47μm2/ms, f 8.44±1.24%, and D 1.30±0.18μm2/ms). Both f and D correlated with ccRCC grading. Conclusion IVIM imaging is able to provide reliable diffusion values in the human kidney and may enhance the accuracy of tumor diagnosis. The D value was the best parameter to distinguish renal tumors from healthy renal tissue. The f value is promising for determining the histological subgroups.